2002
DOI: 10.1177/0310057x0203000211
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Neuromuscular Blockade on Oxygen Supply, Consumption, and Total Chest Compliance in Patients with High Oxygen Requirements Undergoing Mechanical Ventilation

Abstract: We investigated the effects of neuromuscular blockade with atracurium on oxygen consumption, oxygen delivery and total chest compliance in 20 sedated intensive care patients who required mechanical ventilation with an inspired oxygen fraction of at least 0.6.The reverse Fick method was used to measure oxygen consumption. Total chest compliance was measured from the ventilator pneumotachograph and pressure transducer. Measurements were made before neuromuscular blockade, at a standard level of neuromuscular blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
2
2
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The use of deep neuromuscular blockade has been shown to optimize surgical conditions during laparoscopic surgery and soft tissue operations, including hip arthroplasty, as well as yielding optimal conditions for airway management and endoscopic laryngeal surgery [25][26][27]. In addition to improved surgical conditions, use of neuromuscular blockade has been demonstrated to result in decreased blood loss in spine surgery [28] and has been demonstrated to reduce oxygen requirements and improve total lung compliance in critically ill patients [29]. Theoretically, use of neuromuscular blockade can also reduce necessity for a deep anesthetic level to prevent movement and muscle response to surgical stimulation in the nonparalyzed patient [30].…”
Section: Discussionmentioning
confidence: 99%
“…The use of deep neuromuscular blockade has been shown to optimize surgical conditions during laparoscopic surgery and soft tissue operations, including hip arthroplasty, as well as yielding optimal conditions for airway management and endoscopic laryngeal surgery [25][26][27]. In addition to improved surgical conditions, use of neuromuscular blockade has been demonstrated to result in decreased blood loss in spine surgery [28] and has been demonstrated to reduce oxygen requirements and improve total lung compliance in critically ill patients [29]. Theoretically, use of neuromuscular blockade can also reduce necessity for a deep anesthetic level to prevent movement and muscle response to surgical stimulation in the nonparalyzed patient [30].…”
Section: Discussionmentioning
confidence: 99%
“…Some form of continued neuromuscular relaxation could, in these circumstances, be essential. However, in a study of the effect of neuromuscular block on oxygen supply, oxygen consumption, and total chest compliance in patients with high oxygen requirements undergoing mechanical ventilation in the ICU, it was found that neuromuscular block could not be assumed to reduce the oxygen requirements or improve total lung compliance [9].…”
Section: Discussionmentioning
confidence: 99%
“…Atracurium is a neuromuscular blockade widely used to provide muscle relaxation during surgery and in critically ill patients [9,27]. Pharmacokinetic studies have shown that below the usual therapeutic dose (0.5 mg/kg for pediatric patients and 0.6 mg/kg for adult patients), atracurium produces maximum neuromuscular blocking effect 3-5 min following injection, and recovery is generally 95% complete 1 h postinjection [9,12,24,25].…”
Section: Introductionmentioning
confidence: 99%